FRAMING THE FEMALE REPORTER: POWER, GENDER AND JOURNALISM IN HINDI CINEMA - Rajkumar, Johnson (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The representation of women journalists in cinema offers a lens through which the intersections of gender and media can be examine in contemporary society. While journalism in Hindi films has often been used as a narrative device to critique corruption, expose hidden truths and dramatise societal tensions, the figure of the female journalist embodies a more complex negotiation of authority, morality and identity. This article analyses the portrayal of women reporters in Page 3 (2005) and No One Killed Jessica (2011) to explore how cinematic narratives construct and contest women’s roles in the newsroom and the wider public sphere. Through close textual analysis, the article studies how these films represent women journalist between depicting them as vulnerable truth-seekers and empowered crusaders, thereby reflecting broader cultural anxieties about female authority in India’s patriarchal media landscape. By situating these representations within debates on women in media industries, the study argues that in Hindi cinema women journalists have agency in their professional’s life but they are circumscribed to the larger structure of patriarchy.